2019
DOI: 10.1016/j.resourpol.2019.101439
|View full text |Cite
|
Sign up to set email alerts
|

The investment-uncertainty relationship in the oil and gas industry

Abstract: JEL classification: C3 G11 Q41 Q43 A B S T R A C TRecent studies of the oil market demonstrate endogeneity of the oil price by modelling it as a function of consumption and precautionary demands and producers' supply. However, studies analysing the effect of oil price uncertainty on investment do not disentangle uncertainties raised by underlying components which play a role in the oil market. Accordingly, this study uses a new approach to investigate the relationship between investment and uncertainty for a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…The study concluded that the dominant role of oil price is one of the engines driving economic growth in Nigeria. Ahmadi et al (2018), studied the relationship between investment and uncertainty in the United States oil and gas industry using the SVAR-GARCH model. Their results revealed that oil market uncertainty lowers investment only when it is caused by global consumption demand shocks, while market uncertainty is found to have a negative effect on investment with a one-year lag.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study concluded that the dominant role of oil price is one of the engines driving economic growth in Nigeria. Ahmadi et al (2018), studied the relationship between investment and uncertainty in the United States oil and gas industry using the SVAR-GARCH model. Their results revealed that oil market uncertainty lowers investment only when it is caused by global consumption demand shocks, while market uncertainty is found to have a negative effect on investment with a one-year lag.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Zhang et al (2019) proposed soft consensus cost models for Group Decision Making (GDM) processes to aid decision makers in investment purposes in the financial market because it consider cost from both perspectives of a moderator and individual experts. Ahmadi et al (2018) identified three characteristics associated with making investment decisions to be the cost of an investment, the uncertainty over likely future profits and the seeking of additional information in order to reduce this uncertainty. These are provided by stockbrokers, accountants, financial analysts, financial econometricians and financial time series analysts by sometime based on experiences of the financial market over the years which may be subjective and not scientific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation in developing countries has made investors to paly safe in investment uncertainty. Ahmadi et al (2018) identified three characteristics of investment decision as Cost of investment, uncertainty over future profits and seeking for additional information to reduce uncertainty. These and many more are provided by stock brokers, accountants, financial analyst and financial econometricians and financial time series analysts.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria as a country that depended more on oil (Adenomon, 2016) and a major player in the oil market (Ahmadi et al, 2018), investors in Nigeria have invested and are still investing in stock of oil company such as Total Petroleum Company of Nigeria.…”
Section: Introductionmentioning
confidence: 99%